2022
DOI: 10.1111/dom.14785
|View full text |Cite
|
Sign up to set email alerts
|

C‐peptide determination in the diagnosis of type of diabetes and its management: A clinical perspective

Abstract: Impaired beta-cell function is a recognized cornerstone of diabetes pathophysiology. Estimates of insulin secretory capacity are useful to inform clinical practice, helping to classify types of diabetes, complication risk stratification and to guide treatment decisions.Because C-peptide secretion mirrors beta-cell function, it has emerged as a valuable clinical biomarker, mainly in autoimmune diabetes and especially in adult-onset diabetes.Nonetheless, the lack of robust evidence about the clinical utility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 137 publications
0
37
1
Order By: Relevance
“…19 It will also stratify the intensity of insulin regimen required. 20 For example, in patients with type 2 diabetes, a fasting C-peptide below 360pmol/L was more likely to indicate a requirement for basal-bolus regimen than a basalonly insulin regimen. 21 While it may be impractical to measure paired serum glucose and C-peptide on every patient starting on an SGLT2 inhibitor, it may be more pragmatic to consider this test in patients who have additional risk factors for developing DKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 It will also stratify the intensity of insulin regimen required. 20 For example, in patients with type 2 diabetes, a fasting C-peptide below 360pmol/L was more likely to indicate a requirement for basal-bolus regimen than a basalonly insulin regimen. 21 While it may be impractical to measure paired serum glucose and C-peptide on every patient starting on an SGLT2 inhibitor, it may be more pragmatic to consider this test in patients who have additional risk factors for developing DKA.…”
Section: Discussionmentioning
confidence: 99%
“…It would be important to repeat his C‐peptide levels after recovery of his illness as C‐peptide may recover in patients following ketoacidosis 19 . It will also stratify the intensity of insulin regimen required 20 . For example, in patients with type 2 diabetes, a fasting C‐peptide below 360pmol/L was more likely to indicate a requirement for basal‐bolus regimen than a basal‐only insulin regimen 21 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, measurement of C-peptide is of a certain value in clinical practice, such as recognizing T1DM when autoantibodies present as a false negative, predicting the response to insulin treatment and assisting with complication risk stratification in T2DM. 33 RCS curves showed the cut-off values of 2hPCP, ΔCP, and PCGR (2.92 ng/mL, 1.86 ng/mL, and 1.11, respectively), meaning that kidney function progression would accelerate if the level of C-peptide were lower than the above threshold values. Data from a T1DM study have shown that a random C-peptide concentration of ≥0.20 nmol/L, compared with a random C-peptide concentration of <0.005 nmol/L, was associated with a 50% decreased risk for retinopathy, 34 but there has been little research on the relationship between C-peptide values and nephropathy risk in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, measurement of C-peptide is of a certain value in clinical practice, such as recognizing T1DM when autoantibodies present as a false negative, predicting the response to insulin treatment and assisting with complication risk stratification in T2DM 33. RCS curves showed the cut-off values of 2hPCP, ΔCP, and PCGR (2.92 ng/mL, 1.86 ng/mL, and 1.11, respectively), meaning that kidney function progression would accelerate if the level of C-peptide were lower than the above threshold values.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to insulin, C-peptide exhibits a prolonged biological halflife; therefore, its plasma concentrations are higher compared to insulin [1]. In clinical routine, C-peptide measurements are used to assess endogenous insulin secretion, to distinguish between type 1, type 2, and other specific types of diabetes, and for differential diagnosis of fasting hypoglycemia [1][2][3][4]. C-peptide is also used for the calculation of HOMA (homeostatic model assessment) indices (e. g., HOMA-2B or HOMA-IR), i. e., for estimating insulin secretion and insulin resistance, especially in patients on insulin therapy.…”
Section: Introductionmentioning
confidence: 99%